Speech by the Honourable Chief Minister,Penang at the Anniversary Dinner of the Association of Justices of the Peace, State of Penang, to be held at the Edinburgh Room, Hotel Merlin, On Saturday 12th June, 1976 at 8.00 p.m. - Lim, Chong Eu (1976)
I am privileged to be given the opportunity of replying on behalf of the guests present at the Annual Dinner to celebrate the 13th Anniversary of the Justices of the Peace Association State of Penang.